TRANSFORMATIONAL LEADERSHIP AND SOCIAL CAPITAL: IS IT IMPORTANT FOR INNOVATION? (Case Study on Coffe Farmers Member of Koperasi Tani Benteng Alla, Enrekang Regency, South Sulawesi) - Haris, Andi Tenri Ellyana; Prasetya, Arik; Mawardi, Muhammad Kholid (The International Journal of Accounting and Business Society, 2021)
Purpose —  This research aims to explain the influence of transformational leadership and social capital of the leader for innovation that has been applied to coffe farmers who are members of Koperasi Tani Benteng Alla in Enrekang Regency, South Sulawesi.Design/methodology/approach —  Research methods by using a descriptive qualitative purposive sampling and snowball sampling approach with 21 informants that is the chairman of Koperasi Tani Benteng Alla, head of the farmer group and member of farmer group. The researcher used triangulation, member checking and comparing the information in the field as a test of data validation.Findings —  The results of this study showed that the leader with transformation style and have a good social capital will easily to influence his members to do innovations. The chairman of Koperasi Tani Benteng Alla as a leader has a good transformation style and social capital that has a positive impact on the implementation of innovation for his members. Practical implications — innovation should be created through good synergy between transformational leaders who have a vision of change and are supported by the trust of members who are built up through social interaction.Originality/value — This study is to strengthen existing theories and previous research on the important role of transformational leaders and social capital have to execute innovation.Keywords —  Transformational leadership, social capital, innovation.Paper type — Case Study